The Relationship between the Intensity of Gadget Use, Eating Patterns, Mukbang Watching Habits and Changes in Eating Behavior with the Incidence of Overweight in Adolescents - Rakhman, Aulia; Buludawa, Magfirah; Hijra, Hijra; Ariani, Ariani; Megasari, Anitatia Ratna (Journal of Health and Nutrition Research, 2024)
The increasing cases of overweight and obesity are caused by nutritional imbalances. Other factors such as screen time for 2 hours or more every day are studied to increase the risk of obesity by 23%. The mukbang phenomenon has also been shown to change eating behavior in a negative direction, thus risking health problems. This study aims to determine the relationship between the intensity of gadget use, eating patterns, mukbang watching habits and changes in eating behavior with the incidence of overweight in adolescents at SMA Negeri 4 Palu. This study uses a quantitative method with a cross-sectional research design. The population in this study was 392 and a sample of 195 respondents using the proportional random sampling technique. Data collection was carried out using a gadget use intensity questionnaire, FFQ and a mukbang watching habit questionnaire. Data analysis used the chi square statistical test. The results showed that 74 respondents had overweight status (37.9%) and 121 respondents had normal nutritional status (62.1%). Based on the chi square test, the variables that had a relationship with the incidence of overweight were eating patterns (p = 0.006) and mukbang watching habits (p = 0.007). Meanwhile, variables that have no relationship with overweight incidence are the intensity of gadget use (p = 0.324) and changes in eating behavior (p = 0.346). For adolescents, it is expected to avoid sedentary lifestyle habits and apply a diet according to the principles of balanced nutrition.